BAYI TABUNG DALAM PANDANGAN ISLAM - Muh. Idris (Al-'Adl, 2019)
The urgency of this study looks further at the current problem regarding IVF, which until now is still reaping polemics. The analytical method used is descriptive with the results of analysis of findings that legally, babies produced from insemination have two kinds, namely permitted with records of sperm taken from sperm originating from legitimate husband and wife, and planted in the womb of the wife (not the womb of people others) and is not permitted, if the donations are from other men as well as from other women. The author's views on IVF that it is okay provided that the sperm taken is sperm that comes from a legitimate husband and wife, and planted in the womb of the wife (not the womb of another person) and also handle it is a doctor who is an expert from women is not allowed and the opposite sex (man).